C-reactive protein/albumin ratio is associated with lung function among children/adolescents with cystic fibrosis: a three-year longitudinal study - Ventura, Julia Carvalho; Hauschild, Daniela Barbieri; Moreira, Emília Addison Machado; Rosa, Anauã Franco; Barbosa, Eliana; Ludwig-Neto, Norberto; Rosa, Julia Salvan da; Fröde, Tânia Silvia; Moreno, Yara Maria Franco (São Paulo Medical Journal, 2018)
BACKGROUND: Chronic lung infections, inflammation and depletion of nutritional status are considered to be prognostic indicators of morbidity in patients with cystic fibrosis. The aim of this study was to investigate the association between inflammatory markers and lung function, nutritional status and morbidity among children/adolescents with cystic fibrosis. DESIGN AND SETTINGS: Prospective three-year longitudinal study conducted in an outpatient clinic in southern Brazil. METHODS: Children/adolescents aged 1-15 years with cystic fibrosis were enrolled. Nutritional status was determined from weight-to-length and body mass index-to-age z-scores and was classified as acceptable, at risk or nutritional failure. Tumor necrosis factor-α, interleukin-1β, myeloperoxidase, C-reactive protein and C-reactive protein/albumin ratio were analyzed. Lung function was evaluated based on the forced expiratory volume in the first second and morbidity according to the number of hospitalizations for pulmonary exacerbation and infections by Pseudomonas aeruginosa. Lung function, nutritional status and morbidity were the outcomes. Odds ratios and 95% confidence intervals were to evaluate the effect of baseline inflammatory markers on the clinical outcomes after three years of follow-up and p-values < 0.05 were considered significant. RESULTS: We evaluated 38 children/adolescents with cystic fibrosis: 55% female; median age (with interquartile range), 3.75 years (2.71-7.00). Children/adolescents with high C-reactive protein/albumin ratio at baseline had odds of 18 (P = 0.018) of presenting forced expiratory volume in the first second ≤ 70% after three years. The other inflammatory markers were not associated with the outcomes. CONCLUSION: C-reactive protein/albumin ratio was associated with forced expiratory volume in the first second ≤ 70% after three years.